P6 5 Evidence for a Diamond Layer in the Mantle of Neptune - McGuire, Joe; Pohl, Alexandra; Toohie, Alexander (Physics Special Topics, 2013)
This paper explores the idea of diamond formation in gas giants. We apply terrestrial experimental data to the theoretical atmospheric composition and structure of Neptune. We conclude that it is feasible that a solid layer of diamond could form in the conditions on Neptune, completely replacing the layer of liquid methane predicted on the planet. This is not in line with current theories but does have some supporting evidence from the scientic community, and further observational data is required.